The role of different virus genotypes in progression of chronic hepatitis C - Nožić Darko; Stamenković Gorana; Bojić Ivanko; Dimitrijević Jovan; Krstić Ljubiša (Vojnosanitetski Pregled)
The relation between HCV genotypes and the progression of chronic hepatitis is still unknown. Some studies implied more pathogenic effect of genotype 1b for the severity of liver inflammation. However, other studies did not show the association between HCV genotype 1b and the severe outcome of HCV infection. The aim of this study was to determine the most frequent genotypes in this environment and their influence on hepatitis C severity. The investigation included 34 patients with histologically confirmed chronic hepatitis C, aged 20-65 (mean 35.0 years). On the basis of patohistological findings, applying the modern classification, the disease activity was graded as: minimal (A1), moderate (A2) and severe (A3). The extent of fibrosis was marked as: absent (F0), mild (F1), moderate (F2) and severe (F3). Genotyping was performed by nested PCR with type-specific primers and LIPA test and verified by sequencing. The most prevailing genotype in our group of patients was 1b (44.1%), followed by genotype 3a (26.4%), genotype 1a (11.7%) and 2a (2.8%). Five patients had mixed genotypes (four 3a/1b, and one 1a/1b). The severity of liver cell necrosis, measured by alanintransferaze (ALT) levels in serum was not related to any of HCV genotypes. There was no statistically significant difference between histological disease activity in relation to HCV genotypes. Stage of the disease was not significantly related to the HCV genotypes. There was a strong association between the degree of fibrosis and the age of patients (p<0.01). These results could indicate that the determination of HCV genotypes was not useful in the estimation of disease severity and that liver biopsy was the most important for the prognosis of the disease.